Potensi Ekstrak Daun Dewa (Gynura Pseudochina Ldc) Sebagai Larvasida Nyamuk Aedes Aegypti Vektor Penyakit Demam Berdarah Dengue - Panghiyangani, Roselina; Rahmiati; Ahda, Noor (Jurnal Kedokteran Indonesia, 2009)
Background: Gods leaf plant (Gynura pseudochina LDC) has active substances including saponin, flavonoid,and etheric oil. These substances have insecticide effect against larvae. Therefore Gods leaf plant canprobably used to control Aedes aegypti mosquito population in its larvae form. This study aimed todetermine the efficacy of Gods leaf extract in killing Aedes aegypti instar IV mosquito larvae.Methods: This was an experimental study. The Gods leaf was macerated to obtain the extract form. Inthis study the concentration levels of Gods leaf were varied including 550 ppm, 1100 ppm, 2200 ppm,4400 ppm, 8800 ppm, respectively. The positive control was temefos 1%, and the negative control wasCMC-Na 1%, each with four replication. The Gods leaf extract was then administered to 25 l Aedesaegypti larvae in each concentration group. This sample was observed for 24 hours. The data on thenumber of killed larvae was analyzed using Kruskal-Wallis dan Mann-Whitney tests.Results: There was no statistical difference in the mean number of killed larvae among differentconcentration (p=0.40). All concentrations could kill the larvae. Mann-Whitney test showed statisticallysignificant difference in the mean number of killed larvae between negative control and eachconcentration group. There was no statistical difference in the number of killed larvae betweenpositive control and the God leaf groups.Conclusion: Gods leaf extract (Gynura pseudochina (LDC) has statistically significant effect on thedeath of A. aegypti instar IV mosquito larvae, therefore can be used as a natural larvacide.Keywords: Gods leaf extract, larvacide, Aedes aegypti instar IV larvae